An input-output analysis of sectoral specialization and trade integration of the Western Balkans economies - Giovanni Mandras; Simone Salotti (Economies, 2020)
The contribution of this paper is twofold. First, it uses the available official Input-Output data for the Western Balkans economies to estimate the output and value added multipliers of the sectors identified as being either current or emerging strengths within the context of Smart Specialisation. These multipliers indicate the potential impact of changes in final demand for certain products and sectors. This permits the identification of the industries associated with high indirect and induced effects, and to form ideas about the sectoral interdependencies of the economies. For instance, it appears that many sectors related to construction are promising in terms of economic potential related to demand-side monetary injections in Albania. Second, a Multi-Regional dataset is used to investigate the international integration of the Western Balkans economies in terms of participation in the Global Value Chains. The latter has increased over time in the region, but it appears that some economies are benefitting relatively more than others from it.
Keywords: C67; F15; 330; global value chain; input-output analysis; Smart Specialization; Western Balkans